Alkali-resistant composite defoaming agent suitable for composite board production and preparation method of alkali-resistant composite defoaming agent
By using alkali-resistant composite defoaming agent in composite plate production, combining the surfactivity of long-chain fatty alcohols and siloxanes with low surface tension of polysiloxanes, traditional defoaming agents are solved in alkaline environments. The silicon spot problem has achieved better defoaming and foam suppression effects.
Patent Information
- Application Number
- CN202411379231.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional silicone defoaming agents are prone to shrinkage and silicon spots in alkaline environments during the production process of composite boards, which cannot meet the defoaming requirements.
A alkali-resistant composite defoaming agent is adopted, including octadecanol, dodecanol, paraffin, mineral oil, silicone oil, MQ silicone resin, vapor phase silica, metal soap and nano-silica enhancer, etc. Components, by combining surfactivity, dispersion and low surface tension, form a stable foam suppression layer to improve the defoaming effect and foam suppression effect.
In an alkaline environment, the stability and durability of the defoaming agent are significantly improved, effectively inhibiting and eliminating foam, and meeting the defoaming needs of composite board production.
Smart Images

Figure BDA0005069474320000091 
Figure BDA0005069474320000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of chemical defoaming, and in particular to an alkali-resistant composite defoaming agent suitable for composite board production and a preparation method thereof. Background Art
[0002] During the production process of composite boards, a large amount of foam is easily formed on the surface or inside of the composite boards, which can easily cause spots or holes to appear on the appearance of the composite boards.
[0003] Traditional silicone defoamers perform well under neutral or weakly alkaline conditions. However, the environment during the production of composite boards is alkaline, and conventional silicone defoamers are prone to shrinkage and silicon spots, which cannot meet the defoaming requirements of the composite board production environment. Summary of the invention
[0004] In order to promote the better application of defoaming agents in the composite board production environment, the present application provides an alkali-resistant composite defoaming agent suitable for composite board production and a preparation method thereof.
[0005] In the first aspect, the present application provides an alkali-resistant composite defoamer suitable for the production of composite boards, which adopts the following technical solution: An alkali-resistant composite defoamer suitable for producing composite boards comprises the following raw materials in parts by weight: 70-90 parts of cetostearyl alcohol, 40-80 parts of behenyl alcohol, 70-90 parts of paraffin, 0.4-0.65 parts of peregal, 5-9 parts of Span, 0.3-0.55 parts of sodium dodecylbenzene sulfonate, 5-9 parts of Tween, 40-55 parts of mineral oil, 10-20 parts of silicone oil, 1-2 parts of fumed silica, 3-5 parts of MQ silicone resin, 560-640 parts of water and 1-3 parts of acrylic emulsion.
[0006] By adopting the above technical solution, the cetostearyl alcohol with a longer carbon chain has better wetting ability, surface activity and dispersibility, and can form a stable foam inhibition layer in the defoamer treatment liquid, thereby improving the defoaming effect and foam inhibition effect of the defoamer. At the same time, the compounding of cetostearyl alcohol and behenyl alcohol can promote the defoaming performance of the defoamer to be better. Compared with other shorter-chain fatty alcohols, cetostearyl alcohol and behenyl alcohol have better stability and durability in defoaming and foam inhibition under alkaline conditions.
[0007] The compounding of cetostearyl alcohol, behenyl alcohol, mineral oil, silicone oil, and MQ silicone resin can combine the surface activity, degassing performance, and dispersing performance of long-chain fatty alcohols with the low surface tension of polysiloxane to reduce the surface tension of the treatment liquid system, spread rapidly on the foam surface, quickly destroy the stability of the foam, and accelerate the bursting of the foam, which can improve the stability and durability of the defoamer in alkaline environments and high temperature conditions. The emulsifier formed by compounding peregal, sodium dodecylbenzene sulfonate, and Tween can help the fatty alcohol, MQ silicone resin, and silicone oil to disperse evenly to form a stable treatment liquid, which can promote the uniform spreading of the defoamer in the alkaline medium and improve the defoaming efficiency and defoaming durability of the defoamer.
[0008] Preferably, the silicone oil is one of dimethyl silicone oil and amino silicone oil.
[0009] By adopting the above technical scheme, dimethyl silicone oil has lower surface tension and higher activity compared with other silicone oils, which can significantly reduce the tension of the foam surface, causing the foam to break quickly, and can quickly and effectively eliminate the foam, while inhibiting the formation of foam and improving the defoaming efficiency of the defoaming agent. At the same time, dimethyl silicone oil has low volatility, good chemical inertness, no physiological toxicity, and can maintain good defoaming ability in the alkaline environment of composite board production. Amino silicone oil can play a role of dispersion and emulsification in the defoamer system. By utilizing the amino group in amino silicone oil, it can have better chemical stability under high temperature and strong alkali, and is not easily destroyed by alkaline media. In the alkaline environment of composite board production, it has a more lasting and stable defoaming ability.
[0010] Preferably, the alkali-resistant composite defoamer raw material further comprises the following components in parts by weight: 0.3-0.8 parts of metal soaps.
[0011] By adopting the above technical solution, metal soaps can help the defoamer to disperse more evenly in the liquid, enhance the wetting performance of the defoamer, and enable the defoamer to more effectively contact the liquid surface with high surface tension, thereby eliminating and inhibiting foam. Metal soaps can improve the stability and durability of the defoamer in an alkaline environment, and can effectively inhibit the formation and stability of foam in a strong alkaline environment.
[0012] Preferably, the metal soap is one of calcium stearate and zinc stearate.
[0013] By adopting the above technical scheme, calcium stearate and zinc stearate in the defoamer can reduce the surface tension of the foam and accelerate the bursting of the foam. At the same time, calcium stearate and zinc stearate have good thermal stability and alkali resistance. In a strong alkaline environment, they can remain active for a long time and are not easy to decompose, thereby improving the alkali resistance and defoaming durability of the defoamer.
[0014] Preferably, the raw material of the alkali-resistant composite defoamer further includes 5-8 parts of ethylene bisstearamide and 3-5 parts of nano-silicon dioxide reinforcing agent.
[0015] By adopting the above technical solution, the nano-silica reinforcing agent and ethylene bisstearamide have good thermal stability, which can enable the prepared defoaming agent to maintain defoaming durability and defoaming stability under high temperature and strong alkaline environment. The nano-silica reinforcing agent added to the defoaming agent raw material can utilize its own strength and large specific surface area to effectively contact the foam and cover the surface of the foam film, quickly destroy the foam, and at the same time can continuously inhibit the regeneration of the foam, thereby improving the defoaming ability and anti-foaming ability of the defoaming agent.
[0016] Preferably, the nano-silica reinforcing agent comprises the following raw materials in parts by weight: 30-40 parts of hydroxypropyl distarch phosphate, 20-30 parts of tetraethyl orthosilicate, 3-5 parts of amino coupling agent, 5-8 parts of phenyl coupling agent, 10-20 parts of styrene-maleic anhydride copolymer, and 5-8 parts of polyethyleneimine.
[0017] By adopting the above technical solution, the silicon dioxide is modified by amino coupling agent and phenyl coupling agent, which can enhance the compatibility and dispersibility of nano-silica reinforcing agent in the defoamer system, reduce the phenomenon of stratification and precipitation, help the silicon dioxide particles to spread better on the foam film, and improve the durability and stability of the defoaming of the defoamer. Hydroxypropyl distarch phosphate can be compounded with silicon dioxide to reduce the surface tension of the defoamer, promote the nano-silica reinforcing agent to penetrate into the foam more effectively, and accelerate the bursting of the foam.
[0018] Preferably, the preparation method of the nano-silica reinforcing agent comprises the following specific steps: mixing hydroxypropyl distarch phosphate with tetraethyl orthosilicate, an amino coupling agent and a phenyl coupling agent, stirring them fully to form a mixed solution, then heating the mixed solution to 60-80°C, adding styrene-maleic anhydride copolymer to mix, keeping the mixture warm for reaction, cooling after the reaction is completed, adding polyethyleneimine and mixing evenly to obtain nano-silica, washing the nano-silica with a non-polar organic solvent, centrifuging and separating the precipitate, and drying to obtain the nano-silica reinforcing agent.
[0019] By adopting the above technical solution and combining polyethyleneimine with silica, the amphiphilic properties of polyethyleneimine can be utilized to reduce the agglomeration of silica particles, improve the dispersibility of the prepared silica in the defoamer system, and thus improve the defoaming durability and stability of the defoamer.
[0020] In a second aspect, the present application provides a method for preparing an alkali-resistant composite defoamer suitable for composite board production, using the following technical solution: A method for preparing an alkali-resistant composite defoamer suitable for composite board production comprises the following specific steps: S1: Pre-mix silicone oil, fumed silica, MQ silicone resin, Span and Tween, heat to 55-65°C and stir to prepare a pre-dispersion; S2: cetostearyl alcohol, behenyl alcohol, paraffin, peregal, sodium dodecylbenzene sulfonate, mineral oil and pre-dispersion are mixed, heated and stirred to form a mixture, the mixture is heated to 100-110° C., water and acrylic emulsion are separated into two parts respectively, one part of the water is added to the mixture and stirred evenly, and then one part of the acrylic emulsion is added to the mixture and stirred evenly to obtain an oil-in-water emulsion; S3: Mix the oil-in-water emulsion with the remaining water, cool it down, measure the viscosity, and then use the remaining acrylic emulsion and sodium hydroxide aqueous solution to adjust the emulsion viscosity until the emulsion viscosity reaches 400-600mPa.s to prepare an alkali-resistant composite defoamer suitable for composite board production.
[0021] By adopting the above technical scheme, the prepared defoamer is not easily destroyed by alkaline media due to the synergistic effect of various components, and has a more lasting defoaming effect and anti-foaming effect when used in an alkaline system.
[0022] Preferably, the preparation method of the alkali-resistant composite defoamer for composite board production comprises the following specific steps: S1: Pre-mix silicone oil, metal soaps, ethylene bisstearamide, nano-silica reinforcing agent, fumed silica, MQ silicone resin, Span and Tween, heat to 55-65°C and stir to prepare a pre-dispersion; S2: cetostearyl alcohol, behenyl alcohol, paraffin, peregal, sodium dodecylbenzene sulfonate, mineral oil and pre-dispersion are mixed, heated and stirred to form a mixture, the mixture is heated to 100-110° C., water and acrylic emulsion are separated into two parts respectively, one part of the water is added to the mixture and stirred evenly, and then one part of the acrylic emulsion is added to the mixture and stirred evenly to obtain an oil-in-water emulsion; S3: Mix the oil-in-water emulsion with the remaining water, cool it down, measure the viscosity, and then use the remaining acrylic emulsion and sodium hydroxide aqueous solution to adjust the emulsion viscosity until the emulsion viscosity reaches 400-600mPa.s to prepare an alkali-resistant composite defoamer suitable for composite board production.
[0023] In summary, this application has the following beneficial effects: 1. Since the present application uses cetostearyl alcohol and behenyl alcohol as long-chain fatty alcohols to be compounded with polysiloxane and silicone oil, the surface activity, degassing performance, and dispersing performance of long-chain fatty alcohols are combined with MQ silicone resin and silicone oil, which are not easily destroyed by alkaline media, thereby promoting the defoaming agent to spread evenly in the alkaline medium, and promoting the defoaming agent to have a more lasting defoaming effect when used in an alkaline system.
[0024] 2. In this application, metal soaps mainly composed of calcium stearate and zinc stearate are added to the defoamer, which can promote the uniform dispersion of the defoamer in the treatment liquid, enhance the wetting properties of the defoamer, accelerate the bursting of foam, and improve the stability and durability of the defoamer in an alkaline environment.
[0025] 3. In this application, nano-silica reinforcing agent and ethylene bis stearamide are used to improve the durability and stability of the defoaming and anti-foaming effects of the defoaming agent. At the same time, the silicon dioxide is modified by amino coupling agent, phenyl coupling agent and hydroxypropyl distarch phosphate to enhance the compatibility and dispersibility of the nano-silica reinforcing agent in the defoaming agent system, which helps the silicon dioxide particles to spread better on the foam film, accelerate the bursting of the foam, and enhance the defoaming and anti-foaming effects of the defoaming agent. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] All raw materials in the examples are commercially available.
[0028] MQ Silicone Resin Purchase Shandong Dayi Chemical Co., Ltd.
[0029] The dimethyl silicone oil is a dimethyl silicone oil having a viscosity of 5000 cst at 25°C.
[0030] The amino silicone oil is an amino silicone oil having a viscosity of 6000 cp at 25°C.
[0031] Ethylene bisstearamide was purchased from Changzhou Kesai Chenggong Plastic Material Co., Ltd. WAX2000.
[0032] The amino coupling agent selected was aminopropyltriethoxysilane.
[0033] The phenyl coupling agent is phenyltrimethoxysilane coupling agent.
[0034] Styrene-maleic anhydride copolymer was purchased from SMA-700 of Huawen Chemical.
[0035] The molecular weight of polyethyleneimine is 300 Da.
[0036] Preparation Example of Nano-Silica Reinforcement Agent Preparation Example 1 The nano silicon dioxide reinforcing agent comprises the following raw materials in parts by weight: 35 kg of hydroxypropyl distarch phosphate, 25 kg of tetraethyl orthosilicate, 4 kg of amino coupling agent, 7 kg of phenyl coupling agent, 15 kg of styrene-maleic anhydride copolymer and 7 kg of polyethyleneimine.
[0037] The preparation method of nano silicon dioxide reinforcing agent comprises the following specific steps: Hydroxypropyl distarch phosphate is mixed with tetraethyl orthosilicate, an amino coupling agent, and a phenyl coupling agent, and stirred thoroughly to form a mixed solution. The mixed solution is then heated to 70°C, styrene-maleic anhydride copolymer is added and mixed, and the mixture is kept warm for reaction for 6 hours. After the reaction is completed, the mixture is cooled, polyethyleneimine is added and mixed evenly to obtain nano-silica. The silica spheres are washed with toluene, centrifuged and precipitated, and dried to obtain a nano-silica enhancer with an average particle size of 50-100 nm.
[0038] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the amount of hydroxypropyl distarch phosphate used in the nano-silica reinforcing agent raw material is 30 kg, the amount of tetraethyl orthosilicate used is 20 kg, the amount of amino coupling agent used is 3 kg, the amount of phenyl coupling agent used is 8 kg, the amount of styrene-maleic anhydride copolymer used is 10 kg, and the amount of polyethyleneimine used is 5 kg.
[0039] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the amount of hydroxypropyl distarch phosphate used in the nano-silica reinforcing agent raw material is 40 kg, the amount of tetraethyl orthosilicate used is 30 kg, the amount of amino coupling agent used is 5 kg, the amount of phenyl coupling agent used is 5 kg, the amount of styrene-maleic anhydride copolymer used is 20 kg, and the amount of polyethyleneimine used is 8 kg.
[0040] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that no amino coupling agent and no phenyl coupling agent are used in the raw material of the nano-silica reinforcing agent.
[0041] The preparation method of nano silicon dioxide reinforcing agent comprises the following specific steps: Hydroxypropyl distarch phosphate and tetraethyl orthosilicate are mixed and stirred thoroughly to form a mixed solution, and then the mixed solution is heated to 70°C, styrene-maleic anhydride copolymer is added and mixed, and the mixture is kept warm for reaction for 6 hours. After the reaction is completed, the mixture is cooled and polyethyleneimine is added and mixed evenly to obtain nano-silica. The silica spheres are washed with toluene, centrifuged and precipitated, and dried to obtain a nano-silica enhancer with an average particle size of 50-100 nm.
[0042] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that polyethyleneimine is not used in the raw material of the nano-silicon dioxide reinforcing agent. Example
[0043] Example 1 This embodiment provides an alkali-resistant composite defoamer suitable for composite board production, including the following raw materials by weight: 80 kg of cetostearyl alcohol, 60 kg of docosanol, 80 kg of paraffin, 0.53 kg of peregal, 8 kg of Span, 0.42 kg of sodium dodecylbenzene sulfonate, 7 kg of Tween, 47 kg of mineral oil, 15 kg of silicone oil, 1.5 kg of fumed silica, 4 kg of MQ silicone resin, 600 kg of water, and 2 kg of acrylic emulsion. The content ratio of cetostearyl alcohol to octadecanol in cetostearyl alcohol is 7:3, cetostearyl alcohol is purchased from Corning 1618 alcohol in Thailand, and docosanol is purchased from BASF in Germany. 22NF, dimethyl silicone oil is used for silicone oil, Span is selected as Span 60, Tween is selected as Tween 60, and mineral oil is purchased from 30# white oil of Nanjing Refinery.
[0044] The preparation method of the alkali-resistant composite defoamer suitable for composite board production comprises the following specific steps: S1: Pre-mix silicone oil, fumed silica, MQ silicone resin, Span and Tween, heat to 60°C and stir for 20 minutes to prepare a pre-dispersion.
[0045] S2: Cetearyl alcohol, behenyl alcohol, paraffin, peregal, sodium dodecylbenzene sulfonate, mineral oil and pre-dispersion are mixed, heated and stirred to form a mixture, the mixture is heated to 105° C., water and acrylic emulsion are evenly divided into components, one portion of water is added to the mixture and stirred for 5 minutes, and then one portion of acrylic emulsion is added and stirred evenly to obtain an oil-in-water emulsion.
[0046] S3: Mix the oil-in-water emulsion with the remaining water, cool it down, measure the viscosity, add the remaining acrylic emulsion, and then adjust the viscosity of the emulsion using a sodium hydroxide aqueous solution with a sodium hydroxide mass fraction of 10% until the emulsion viscosity reaches 500mPa.s, to obtain an alkali-resistant composite defoamer with a solid content of 30% suitable for composite board production.
[0047] Example 2 The difference between Example 2 and Example 1 is that the content ratio of cetyl alcohol to octadecanol in the cetostearyl alcohol in the raw material of the alkali-resistant composite defoamer suitable for the production of composite boards is 3:7.
[0048] Example 3 The difference between Example 3 and Example 1 is that the content ratio of cetyl alcohol to octadecanol in the cetostearyl alcohol raw material suitable for the production of composite boards is 5:5.
[0049] Example 4 The difference between Example 4 and Example 1 is that the amount of cetostearyl alcohol used in the raw material of the alkali-resistant composite defoamer suitable for composite board production is 70 kg, the amount of behenyl alcohol used is 80 kg, the amount of paraffin used is 70 kg, the amount of peregal used is 0.4 kg, the amount of Span used is 9 kg, the amount of sodium dodecylbenzene sulfonate used is 0.3 kg, the amount of Tween used is 9 kg, the amount of mineral oil used is 40 kg, the amount of silicone oil used is 20 kg, the amount of fumed silica used is 1 kg, the amount of MQ silicone resin used is 5 kg, the amount of water used is 560 kg, and the amount of acrylic emulsion used is 1 kg.
[0050] Example 5 The difference between Example 5 and Example 1 is that the amount of cetostearyl alcohol used in the raw material of the alkali-resistant composite defoamer suitable for composite board production is 90 kg, the amount of behenyl alcohol used is 40 kg, the amount of paraffin used is 90 kg, the amount of peregal used is 0.65 kg, the amount of Span used is 5 kg, the amount of sodium dodecylbenzene sulfonate used is 0.55 kg, the amount of Tween used is 5 kg, the amount of mineral oil used is 55 kg, the amount of silicone oil used is 10 kg, the amount of fumed silica used is 2 kg, the amount of MQ silicone resin used is 3 kg, the amount of water used is 640 kg, and the amount of acrylic emulsion used is 3 kg.
[0051] Example 6 The difference between Example 6 and Example 1 is that the silicone oil in the raw material of the alkali-resistant composite defoamer suitable for the production of composite boards is amino silicone oil.
[0052] Example 7 The difference between Example 7 and Example 1 is that the raw material of the alkali-resistant composite defoaming agent suitable for the production of composite boards also includes 0.5 kg of metal soap, wherein the metal soap is calcium stearate.
[0053] The preparation method of the alkali-resistant composite defoamer suitable for composite board production comprises the following specific steps: S1: Pre-mix silicone oil, fumed silica, metal soaps, MQ silicone resin, Span and Tween, heat to 60°C and stir for 20 minutes to prepare a pre-dispersion.
[0054] S2: Cetearyl alcohol, behenyl alcohol, paraffin, peregal, sodium dodecylbenzene sulfonate, mineral oil and pre-dispersion are mixed, heated and stirred to form a mixture, the mixture is heated to 105° C., water and acrylic emulsion are evenly divided into components, one portion of water is added to the mixture and stirred for 5 minutes, and then one portion of acrylic emulsion is added and stirred evenly to obtain an oil-in-water emulsion.
[0055] S3: Mix the oil-in-water emulsion with the remaining water, cool it down, measure the viscosity, add the remaining acrylic emulsion, and then adjust the viscosity of the emulsion using a sodium hydroxide aqueous solution with a sodium hydroxide mass fraction of 10% until the emulsion viscosity reaches 500mPa.s, to obtain an alkali-resistant composite defoamer with a solid content of 30% suitable for composite board production.
[0056] Example 8 The difference between Example 8 and Example 7 is that the metal soap in the raw material of the alkali-resistant composite defoamer suitable for the production of composite boards is zinc stearate.
[0057] Example 9 The difference between Example 9 and Example 7 is that the raw material of the alkali-resistant composite defoamer suitable for the production of composite boards also includes 7 kg of ethylene bisstearamide.
[0058] The preparation method of an alkali-resistant composite defoamer suitable for composite board production comprises the following specific steps: S1: pre-mix silicone oil, fumed silica, metal soaps, ethylene bisstearamide, MQ silicone resin, Span and Tween, heat to 60°C and stir for 20 minutes to prepare a pre-dispersion.
[0059] S2: Cetearyl alcohol, behenyl alcohol, paraffin, peregal, sodium dodecylbenzene sulfonate, mineral oil and pre-dispersion are mixed, heated and stirred to form a mixture, the mixture is heated to 105° C., water and acrylic emulsion are evenly divided into components, one portion of water is added to the mixture and stirred for 5 minutes, and then one portion of acrylic emulsion is added and stirred evenly to obtain an oil-in-water emulsion.
[0060] S3: Mix the oil-in-water emulsion with the remaining water, cool it down, measure the viscosity, add the remaining acrylic emulsion, and then adjust the viscosity of the emulsion using a sodium hydroxide aqueous solution with a sodium hydroxide mass fraction of 10% until the emulsion viscosity reaches 500mPa.s, to obtain an alkali-resistant composite defoamer with a solid content of 30% suitable for composite board production.
[0061] Example 10 The difference between Example 10 and Example 9 is that the raw material of the alkali-resistant composite defoamer suitable for the production of composite boards also includes 4 kg of nano-silicon dioxide reinforcing agent, wherein the nano-silicon dioxide reinforcing agent comes from Preparation Example 1.
[0062] The invention discloses a method for preparing an alkali-resistant composite defoamer suitable for composite board production, comprising the following specific steps: S1: pre-mixing silicone oil, fumed silica, metal soaps, ethylene bisstearamide, MQ silicone resin, nano-silica reinforcing agent, Span and Tween, heating to 60°C and stirring for 20 minutes to prepare a pre-dispersion.
[0063] S2: Cetearyl alcohol, behenyl alcohol, paraffin, peregal, sodium dodecylbenzene sulfonate, mineral oil and pre-dispersion are mixed, heated and stirred to form a mixture, the mixture is heated to 105° C., water and acrylic emulsion are evenly divided into components, one portion of water is added to the mixture and stirred for 5 minutes, and then one portion of acrylic emulsion is added and stirred evenly to obtain an oil-in-water emulsion.
[0064] S3: Mix the oil-in-water emulsion with the remaining water, cool it down, measure the viscosity, add the remaining acrylic emulsion, and then adjust the viscosity of the emulsion using a sodium hydroxide aqueous solution with a sodium hydroxide mass fraction of 10% until the emulsion viscosity reaches 500mPa.s, to obtain an alkali-resistant composite defoamer with a solid content of 30% suitable for composite board production.
[0065] Embodiment 11 The difference between Example 11 and Example 10 is that the amount of ethylene bisstearamide used in the raw material of the alkali-resistant composite defoamer suitable for the production of composite boards is 8 kg, and the amount of the nano-silicon dioxide reinforcing agent used is 3 kg.
[0066] Example 12 The difference between Example 12 and Example 10 is that the amount of ethylene bisstearamide used in the raw material of the alkali-resistant composite defoamer suitable for the production of composite boards is 5 kg, and the amount of the nano-silicon dioxide reinforcing agent used is 5 kg.
[0067] Example 13 The difference between Example 13 and Example 10 is that the nano-silicon dioxide reinforcing agent in the raw material of the alkali-resistant composite defoaming agent suitable for the production of composite boards comes from Preparation Example 2.
[0068] Embodiment 14 The difference between Example 14 and Example 10 is that the nano-silicon dioxide reinforcing agent in the raw material of the alkali-resistant composite defoaming agent suitable for the production of composite boards comes from Preparation Example 3.
[0069] Embodiment 15 The difference between Example 15 and Example 10 is that the nano-silicon dioxide reinforcing agent in the raw material of the alkali-resistant composite defoaming agent suitable for the production of composite boards comes from Preparation Example 4.
[0070] Example 16 The difference between Example 16 and Example 10 is that the nano-silicon dioxide reinforcing agent in the raw material of the alkali-resistant composite defoaming agent suitable for the production of composite boards comes from Preparation Example 5.
[0071] Embodiment 17 The difference between Example 17 and Example 10 is that the nano-silica reinforcing agent in the raw material of the alkali-resistant composite defoaming agent suitable for the production of composite boards is replaced by an equal amount of commercially available nano-silica, and the average particle size of the commercially available nano-silica is 50-100 nm.
[0072] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that an equal amount of cetostearyl alcohol is used instead of behenyl alcohol in the raw material of the alkali-resistant composite defoamer suitable for the production of composite boards.
[0073] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that an equal amount of dodecyl alcohol is used instead of behenyl alcohol in the raw material of the alkali-resistant composite defoamer suitable for the production of composite boards.
[0074] Comparative Example 3 Comparative Example 3 uses the commercially available XST-3940 silicone defoaming agent produced by Fujian Xister New Material Technology Co., Ltd.
[0075] Performance testing According to the alkali-resistant composite defoaming agent suitable for composite board production provided in Examples 1-17 and Comparative Examples 1-3 of the present application, the following performance tests were performed, and the specific test results are shown in Table 1.
[0076] Detection Methods 1. Defoaming and antifoaming performance Use 600ml of foaming medium-composite board water sample, test temperature is 40°C, use a circulating bubble tester to bubble until the foam height reaches 300ml, add the defoamer prepared in this application and record the foam height at different time periods. By recording the change of foam volume V over time, recording the foam height when the foam volume is the lowest to determine the defoaming performance of the sample, and recording the time required for the foam volume to recover to 300ml to determine the anti-foaming performance of the sample.
[0077] Table 1: Performance test results data table It can be seen from the performance test results that the alkali-resistant composite defoamer suitable for composite board production prepared in the present application has good defoaming effect and anti-foaming effect in an alkaline environment.
[0078] By comparing Example 7 with Example 1, it can be seen that metal soaps are added to the raw materials of the alkali-resistant composite defoamer suitable for composite board production prepared in the present application. From the performance test results, it can be seen that the defoamer prepared in the alkaline environment where the composite board is produced has good defoaming and anti-foaming properties.
[0079] It can be seen from Examples 9-14 that the use of ethylene bisstearamide can further improve the defoaming performance of the defoaming agent prepared in the present application.
[0080] By comparing Examples 10-14, it can be seen that compared with other defoaming ingredients, the nano-silicon dioxide enhancer can use its special surface strength and specific surface area to reduce the local surface tension of the foam wall, destroy the self-healing effect of the foam, cause the foam to burst, and further enhance the defoaming effect and anti-foaming effect of the defoamer.
[0081] By comparing Examples 15-17 with Example 10, it can be seen that Example 15 does not use amino coupling agents and phenyl coupling agents, Example 16 does not use polyethyleneimine, and Example 17 uses ordinary commercially available nano-silicon dioxide. From the performance test results, it can be seen that the performance of the prepared defoamers will all decrease. This may be because not using amino coupling agents and phenyl coupling agents can easily cause nano-silicon dioxide particles to agglomerate themselves during the generation process, and not using polyethyleneimine can easily cause the prepared nano-silicon dioxide reinforcing agent to be added to the defoamer system, resulting in poor fluidity and compatibility, causing stratification or precipitation, thereby affecting the defoaming performance of the defoamer.
[0082] By comparing Comparative Examples 1-2 with Example 1, it can be seen that Comparative Example 1 uses an equal amount of cetostearyl alcohol instead of behenyl alcohol, and Comparative Example 2 uses an equal amount of tetradecyl alcohol instead of behenyl alcohol. From the performance test results, it can be seen that the defoaming performance of the defoamer prepared in Comparative Example 1 is significantly reduced, and the anti-foaming performance is also affected, which further proves that the single cetostearyl alcohol has poor defoaming performance in the alkaline environment of composite board production, and the activity of the components in the defoamer system is easily affected. The defoaming and anti-foaming properties of the defoamer prepared in Comparative Example 2 are significantly reduced, and foam is repeatedly generated, which further illustrates that the defoaming effect of using shorter-chain fatty alcohols in an alkaline environment is poor.
[0083] From Comparative Example 3, it can be seen that the defoaming and defoaming effects of common commercially available silicone defoamers in the composite board production environment are poor, foam is repeatedly generated, and silicon precipitation occurs. This further illustrates that traditional silicone defoamers cannot meet the requirements of defoaming and defoaming in the alkaline environment of composite board production.
[0084] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An alkali-resistant composite defoamer suitable for composite board production, characterized in that: The invention comprises the following raw materials in parts by weight: 70-90 parts of cetostearyl alcohol, 40-80 parts of behenyl alcohol, 70-90 parts of paraffin, 0.4-0.65 parts of peregal, 5-9 parts of Span, 0.3-0.55 parts of sodium dodecylbenzene sulfonate, 5-9 parts of Tween, 40-55 parts of mineral oil, 10-20 parts of silicone oil, 1-2 parts of fumed silica, 3-5 parts of MQ silicone resin, 560-640 parts of water and 1-3 parts of acrylic emulsion.
2. The alkali-resistant composite defoamer suitable for composite board production according to claim 1, characterized in that: The silicone oil is one of dimethyl silicone oil and amino silicone oil.
3. The alkali-resistant composite defoamer suitable for composite board production according to claim 1, characterized in that: The alkali-resistant composite defoamer raw material also includes the following components in parts by weight: 0.3-0.8 parts of metal soaps.
4. The alkali-resistant composite defoamer suitable for composite board production according to claim 3, characterized in that: The metal soap is one of calcium stearate and zinc stearate.
5. The alkali-resistant composite defoamer suitable for composite board production according to claim 1, characterized in that: The raw materials of the alkali-resistant composite defoamer also include 5-8 parts of ethylene bisstearamide and 3-5 parts of nano silicon dioxide reinforcing agent.
6. The alkali-resistant composite defoamer suitable for composite board production according to claim 5, characterized in that: The nano-silicon dioxide reinforcing agent comprises the following raw materials in parts by weight: 30-40 parts of hydroxypropyl distarch phosphate, 20-30 parts of tetraethyl orthosilicate, 3-5 parts of amino coupling agent, 5-8 parts of phenyl coupling agent, 10-20 parts of styrene-maleic anhydride copolymer, and 5-8 parts of polyethyleneimine.
7. The alkali-resistant composite defoamer suitable for composite board production according to claim 6, characterized in that: The preparation method of the nano silicon dioxide reinforcing agent comprises the following specific steps: mixing hydroxypropyl distarch phosphate with tetraethyl orthosilicate, an amino coupling agent and a phenyl coupling agent, stirring fully to form a mixed solution, then heating the mixed solution to 60-80°C, adding styrene-maleic anhydride copolymer to mix, keeping the temperature to react, cooling after the reaction is completed, adding polyethyleneimine to mix evenly to obtain nano silicon dioxide, washing the nano silicon dioxide with a non-polar organic solvent, centrifugally separating the precipitation, and drying to obtain the nano silicon dioxide reinforcing agent.
8. A method for preparing an alkali-resistant composite defoamer suitable for composite board production as claimed in any one of claims 1 to 7, characterized in that: The specific steps include: S1: Pre-mix silicone oil, fumed silica, MQ silicone resin, Span and Tween, heat to 55-65°C and stir to prepare a pre-dispersion; S2: cetostearyl alcohol, behenyl alcohol, paraffin, peregal, sodium dodecylbenzene sulfonate, mineral oil and pre-dispersion are mixed, heated and stirred to form a mixture, the mixture is heated to 100-110° C., water and acrylic emulsion are divided into two parts respectively, one part of water is added to the mixture and stirred evenly, and then one part of acrylic emulsion is added to the mixture and stirred evenly to obtain an oil-in-water emulsion; S3: Mix the oil-in-water emulsion with the remaining water, cool it down, measure the viscosity, and then use the remaining acrylic emulsion and sodium hydroxide aqueous solution to adjust the emulsion viscosity until the emulsion viscosity reaches 400-600mPa.s to prepare an alkali-resistant composite defoamer suitable for composite board production.
9. The method for preparing the alkali-resistant composite defoamer suitable for composite board production according to claim 8, characterized in that: The specific steps include: S1: Pre-mix silicone oil, metal soaps, ethylene bisstearamide, nano-silica reinforcing agent, fumed silica, MQ silicone resin, Span and Tween, heat to 55-65°C and stir to prepare a pre-dispersion; S2: cetostearyl alcohol, behenyl alcohol, paraffin, peregal, sodium dodecylbenzene sulfonate, mineral oil and pre-dispersion are mixed, heated and stirred to form a mixture, the mixture is heated to 100-110° C., water and acrylic emulsion are divided into two parts respectively, one part of water is added to the mixture and stirred evenly, and then one part of acrylic emulsion is added to the mixture and stirred evenly to obtain an oil-in-water emulsion; S3: Mix the oil-in-water emulsion with the remaining water, cool it down, measure the viscosity, and then use the remaining acrylic emulsion and sodium hydroxide aqueous solution to adjust the emulsion viscosity until the emulsion viscosity reaches 400-600mPa.s to prepare an alkali-resistant composite defoamer suitable for composite board production.
